Commercial users of functional programming workshop report. Issue 6 (8th January 2014) - SPERBER, MICHAEL; MADHAVAPEDDY, ANIL
Abstract : Commercial Users of Functional Programming (CUFP) is an annual workshop that is aimed at the community of software developers who use functional programming in real-world settings. This scribe report covers the talks that were delivered at the 2012 workshop, which was held in association with International Conference on Functional Programming (ICFP) in Copenhagen, Denmark. The goal of the report is to give the reader a sense of what went on, rather than to reproduce the full details of the talks. Videos and slides from all the talks are available online at http://cufp.org.